2005
DOI: 10.1104/pp.105.067884
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Thioredoxin Is Required for Nodule Development to Reduce Reactive Oxygen Species Levels in Soybean Roots

Abstract: Nodules are formed on legume roots as a result of signaling between symbiotic partners and in response to the activities of numerous genes. We cloned fragments of differentially expressed genes in spot-inoculated soybean (Glycine max) roots. Many of the induced clones were similar to known genes related to oxidative stress, such as thioredoxin and b-carotene hydroxylase. The deduced amino acid sequences of full-length soybean cDNAs for thioredoxin and b-carotene hydroxylase were similar to those in other speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 47 publications
0
49
0
Order By: Relevance
“…In legume roots, antioxidant proteins such as SOD, CAT and thioredoxin play an important role during nodule formation and show increased expression in nodules necessary for lowering the reactive oxygen species levels (Lee et al, 2005). A reduced expression of the thioredoxin gene via RNA interference resulted in impaired nodule formation (Lee et al, 2005). Similar to root nodules, where the symbiotic relationships occurs between bacteria and plant, preserved antioxidant genes of Symbiodinium suggest that perhaps these antioxidants are important in the establishment of coral-algal symbiosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In legume roots, antioxidant proteins such as SOD, CAT and thioredoxin play an important role during nodule formation and show increased expression in nodules necessary for lowering the reactive oxygen species levels (Lee et al, 2005). A reduced expression of the thioredoxin gene via RNA interference resulted in impaired nodule formation (Lee et al, 2005). Similar to root nodules, where the symbiotic relationships occurs between bacteria and plant, preserved antioxidant genes of Symbiodinium suggest that perhaps these antioxidants are important in the establishment of coral-algal symbiosis.…”
Section: Discussionmentioning
confidence: 99%
“…The Trx enzymes in the chloroplast regulate the activity of photosynthetic enzymes via ferreodoxin-thioredoxin reductase (Arnér and Holmgren, 2000). In legume roots, antioxidant proteins such as SOD, CAT and thioredoxin play an important role during nodule formation and show increased expression in nodules necessary for lowering the reactive oxygen species levels (Lee et al, 2005). A reduced expression of the thioredoxin gene via RNA interference resulted in impaired nodule formation (Lee et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…An N-terminal region of 250-bp sequence conserved in all three GmS6K1 paralogs ( Supplementary Fig. 2, dashed arrows) was chosen for the interference and introduced into Agrobacterium rhizogenes to form transgenic hairy roots of soybean (Lee et al, 2005) after being cloned downstream of a nodule-specific leghemoglobin (Lbc3) promoter. Significantly impaired nodulation was observed in GmS6K1-RNAi roots with apparent reduction in both weight and number of nodules (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The GmS6K1-RNAi construct was transferred into the binary plasmid pCAMBIA1304 which contained 35S-GUS, and the resulting plasmid was introduced into Agrobacterium rhizogenes (K599) by the freeze-thaw method. Transgenic root nodules containing the GmS6K1-RNAi construct were produced as previously described (Lee et al, 2005).…”
Section: Generation Of Transgenic Root Nodulesmentioning
confidence: 99%
“…2A; Lee et al, 2005). In a BLAST search with the GmBCH1 sequence against the soybean genome (http://www.phytozome.net/ soybean.php; Schmutz et al, 2010), we found several open reading frames encoding products with amino acid sequences highly homologous to that of GmBCH1; they were designated GmBCH2 to GmBCH5 (GenBank accession numbers are as follows:…”
Section: Expression Of Genes Encoding Putative Bchs In Soybeanmentioning
confidence: 99%